Mutations in Multidomain Protein MEGF8 Identify a Carpenter Syndrome Subtype Associated with Defective Lateralization - ELÇİOĞLU, HURİYE NURSEL (CELL PRESS, 2012)
Carpenter syndrome is an autosomal-recessive multiple-congenital-malformation disorder characterized by multisuture craniosynostosis and polysyndactyly of the hands and feet; many other clinical features occur, and the most frequent include obesity, umbilical hernia, cryptorchidism, and congenital heart disease. Mutations of RAB23, encoding a small GTPase that regulates vesicular transport, are present in the majority of cases. Here, we describe a disorder caused by mutations in multiple epidermal-growth-factor-like-domains 8 (MEGF8), which exhibits substantial clinical overlap with Carpenter syndrome but is frequently associated with abnormal left-right patterning. We describe five affected individuals with similar dysmorphic facies, and three of them had either complete situs inversus, dextrocardia, or transposition of the great arteries; similar cardiac abnormalities were previously identified in a mouse mutant for the orthologous Megf8. The mutant alleles comprise one nonsense, three missense, and two splice-site mutations; we demonstrate in zebrafish that, in contrast to the wild-type protein, the proteins containing all three missense alterations provide only weak rescue of an early gastrulation phenotype induced by Megf8 knockdown. We conclude that mutations in MEGF8 cause a Carpenter syndrome subtype frequently associated with defective left-right patterning, probably through perturbation of signaling by hedgehog and nodal family members. We did not observe any subject with biallelic loss-of function mutations, suggesting that some residual MEGF8 function might be necessary for survival and might influence the phenotypes observed.
Keywords: EPIDERMAL-GROWTH-FACTOR; CRYSTAL-STRUCTURE; KELCH DOMAIN; OPEN BRAIN; RAB23; MOUSE; SYNOSTOSIS; SPECTRUM; GTPASES; GLI3